Earth Called - Cast, P. C (New York Wednesday Books, 2023)
"In this last installment of the Tales of a New World series, love and goodness are put to the ultimate test as gods, humans, and animals come together to save everything they hold dear"--
The God of Death and his terrifying army are marching ever closer in Death's quest to rule the Wind Rider Plains-- and to kill or enslave anyone who stands in his way. Mari, Niki, and their newly formed Pack have only one hope: Ralina, Death's Storyteller. The woman Death has forced to travel at his side, recording every atrocity he commits. Ralina has escaped, and warns the Pack and the Wind Riders with the knowledge she has accumulated. But is there any way to truly stop the God of Death? Gods, human, and animals must come together to save everything they hold dear. -- adapted from jacket
Sequel to: Wind rider
Ages 12-18.
111711
Keywords: Healers -- Fiction; Magic -- Fiction; Alliances -- Fiction; Young adult fiction; Imaginary wars and battles -- Juvenile fiction; Juvenile Fiction -- General; Fantasy fiction; Fiction; Juvenile works; Novels